In Vitro Osteogenic Properties of Two Dental Implant Surfaces - Monjo, Marta; Petzold, Christiane; Ramis, Joana Maria; Lyngstadaas, Staale Petter; Ellingsen, Jan Eirik (International Journal of Biomaterials, 2012)
Current dental implant research aims at understanding the biological basis for successful implant therapy. The aim of the study was to perform a full characterization of the effect of two commercial titanium (Ti) surfaces, OsseoSpeed and TiOblast, on the behaviour of mouse preosteoblast MC3T3-E1 cells. The effect of these Ti surfaces was compared with tissue culture plastic (TCP). In vitro experiments were performed to evaluate cytotoxicity, cell morphology and proliferation, alkaline phosphatase activity, gene expression, and release of a wide array of osteoblast markers. No differences were observed on cell viability and cell proliferation. However, changes were observed in cell shape after 2 days, with a more branched morphology on OsseoSpeed compared to TiOblast. Moreover, OsseoSpeed surface increased BMP-2 secretion after 2 days, and this was followed by increased IGF-I, BSP, and osterix gene expression and mineralization compared to TiOblast after 14 days. As compared to the gold standard TCP, both Ti surfaces induced higher osteocalcin and OPG release than TCP and differential temporal gene expression of osteogenic markers. The results demonstrate that the gain of using OsseoSpeed surface is an improved osteoblast differentiation and mineralization, without additional effects on cell viability or proliferation.